2009
DOI: 10.1111/j.1398-9995.2009.02118.x
|View full text |Cite
|
Sign up to set email alerts
|

Mastocytosis and insect venom allergy: diagnosis, safety and efficacy of venom immunotherapy

Abstract: The most important causative factor for anaphylaxis in mastocytosis are insect stings. The purpose of this review is to analyse the available data concerning prevalence, diagnosis, safety and effectiveness of venom immunotherapy (VIT) in mastocytosis patients. If data were unclear, authors were contacted personally for further information. Quality of evidence (A: high, B: moderate, C: low and D: very low) and strength of recommendation (strong 1 and weak 2) concerning VIT in mastocytosis patients are assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 61 publications
(144 reference statements)
4
88
2
8
Order By: Relevance
“…Even though patients with indolent systemic mastocytosis have an almost normal life expectancy, significant danger may arise from anaphylactic reactions. [27][28][29][30] In a recent study, Brockow et al 30 found a cumulative incidence of anaphylaxis of up to 49% in adults with systemic mastocytosis leading to the recommendation to carry an emergency medication set, including epinephrine. Severe and even fatal intra-and postoperative complications also pose an important threat.…”
Section: Discussionmentioning
confidence: 99%
“…Even though patients with indolent systemic mastocytosis have an almost normal life expectancy, significant danger may arise from anaphylactic reactions. [27][28][29][30] In a recent study, Brockow et al 30 found a cumulative incidence of anaphylaxis of up to 49% in adults with systemic mastocytosis leading to the recommendation to carry an emergency medication set, including epinephrine. Severe and even fatal intra-and postoperative complications also pose an important threat.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Given the likelihood that HVA is IgE mediated in most mastocytosis patients, venom immunotherapy has been proposed as a treatment of choice, albeit with important caveats. 59,[66][67][68] General guidelines for the diagnosis and management of HVA are available, although they are not specific to mastocytosis patients. 69 I pursue full investigation for SM including BM biopsy in patients with anaphylaxis after Hymenoptera stings, regardless of tryptase level or presence of MIS.…”
Section: Malabsorption With Weight Loss Due To Gastrointestinal Mast mentioning
confidence: 99%
“…These mediator-targeting drugs are prescribed according to published algorithms [21, 25- blockers (usually IV) are often administered. In patients with mastocytosis in whom an IgE-dependent allergy against hymenoptera venom has been detected, life-long immunotherapy should be performed with recognition of potential side effects, such as increased prevalence of local or systemic allergic reactions [60][61][62][63]. In patients with inhalant allergies and symptoms of allergic rhinitis, the safety and efficacy of immunotherapy has not been systemically studied, but the risk-versus-benefit ratio is generally not considered to be favorable to warrant inhalant immunotherapy, and the treatment plan has to be based on the individual situation in each case.…”
Section: Prophylactic Therapy and Immunotherapymentioning
confidence: 99%